Factors influencing seed germination in Cerrado grasses - Kolb, Rosana Marta [UNESP]; Pilon, Natashi Aparecida Lima; Durigan, Giselda (FapUNIFESP (SciELO), 2016)
Few studies address the ecology of herbs of Cerrado grasslands, which are ecosystems where the long dry season, high temperatures, insolation, fire and invasive grasses greatly influencing germination and the establishment of plants. We assessed germination of 13 species of Poaceae from Cerrado grasslands under nursery conditions or in germination chambers, the latter with i) recently collected seeds and seeds after six months storage, ii) under constant and alternating temperatures, and iii) in the presence and absence of light. Germinability, mean germination time (MGT) and required light were quantified to elucidate factors involved in successful germination. Germinability was low for most grasses, probably because of low seed viability. For most species, germinability and MGT were not altered by seed storage. Germination percentages were higher at alternating temperatures and in the presence of light, factors that are more similar to natural environmental situations compared with constant temperature or the absence of light. Our findings indicate that alternating temperatures and light incidence are key factors for germination of species of Poaceae. The maintenance of these environmental factors, which are crucial for the conservation of Cerrado grasslands, depends on appropriate management interventions, such as fire management and the control of biological invasion.
Keywords: Conservation; Grasslands; Poaceae; Savanna; Seed storage; Seed viability